Arts and Technology First International Conference, ArtsIT 2009, Yi-Lan, Taiwan, September 24-25, 2009, Revised Selected Papers - Huang, Fay; Wang, Reen-Cheng (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering,, 2010)
This book constitutes the thoroughly refereed post-conference proceedings of the First International Conference on Arts and Technology, ArtsIT 2009, which was held in September 2009 in Yi-Lan, Taiwan. The 33 revised full papers presented were carefully reviewed and selected from about 50 submissions. These papers cover various topics such as New Media Technologies (tracking sensors, wearable computers, mixed reality), Software Art (Image processing or computer graphics techniques that create arts, including algorithmic art, mathematic art, advanced modeling and rendering), Animation Techniques (2D or 3D computer animations, AI-based animations), Multimedia (Integration of different media, such as virtual reality systems, audio, performing arts) as well as Interactive Methods (Vision-based tracking and recognition, interactive art).